2018
DOI: 10.1093/cid/ciy768
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Extended-spectrum Beta-lactamase–producing Enterobacteriaceae and the Risk of Surgical Site Infection After Colorectal Surgery: A Prospective Cohort Study

Abstract: ESBL-PE carriers who receive cephalosporin-based prophylaxis are at increased risk of SSI following colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 24 publications
1
34
1
Order By: Relevance
“…Studies from Europe suggest that ESBL enteric colonization ranges between 18% and 29% among patients who undergo colorectal surgery, with a 2-fold increase in deep SSI among patients with enteric ESBL-producing Enterobacteriaceae colonization. 10,11 Similar to a previous study, 11 the risk of SSI, particularly deep SSI, remains high in ESBL-prevalent regions. On the contrary, our population included all patients who underwent clean-contaminated, contaminated, or dirty abdominal surgical procedures.…”
Section: Discussionsupporting
confidence: 79%
“…Studies from Europe suggest that ESBL enteric colonization ranges between 18% and 29% among patients who undergo colorectal surgery, with a 2-fold increase in deep SSI among patients with enteric ESBL-producing Enterobacteriaceae colonization. 10,11 Similar to a previous study, 11 the risk of SSI, particularly deep SSI, remains high in ESBL-prevalent regions. On the contrary, our population included all patients who underwent clean-contaminated, contaminated, or dirty abdominal surgical procedures.…”
Section: Discussionsupporting
confidence: 79%
“…Further, anastomosis creation was shown to result in a 200- and 500-fold increase in the relative abundance of Enterococcus and Escherichia/Shigella, respectively, in a rodent model[36]. In a prospective multicentric cohort of patients undergoing colorectal surgery, including our center, Dubinsky-Pertzov et al[37] showed that carriers of beta lactamase-producing Enterobacteriaceae receiving cephalosporin-based antibioprophylaxsis were at risk of surgical site infection [odds ratio (OR) 2.36]. These findings suggest that changes in the local microbiome caused by surgery or unappropriate prophylactic antibiotherapy might worsen the situation of patients with already unfavorable microbiome profiles.…”
Section: Preoperative Measures To Prevent Almentioning
confidence: 99%
“… 73 , 74 There are also uncertainties regarding whether AMR surveillance should drive antibiotic surgical prophylaxis against MDR Gram-negative bacteria, although more evidence is available on the increased risk of surgical site infections in MDR Gram-negative carriers. 75 , 76 AMR surveillance data on screening isolates can be useful for the AMS team to individualize surgical prophylaxis practice in selected cases.…”
Section: Resultsmentioning
confidence: 99%